Projective transformations of a plane - Burban, Igor; Duma, W. (U sviti Mathematyky)

Projective transformations of a plane and three-dimensional space - Burban, Igor; Duma, W. (U sviti Mathematyky)

Rational parameterization of algebraic curves - Burban, Igor (U sviti Mathematyky)

Invariant Cones in Real Representations - Hilgert, Joachim; Neeb, K.-H. (Positivity in Lie Theory: Open Problems)

Reproducing Kernels on Vector Bundles - Hilgert, Joachim; Bertram, W. (Lie Theory and its Applications in Physics)

Hardy Spaces and Analytic Continuation of Bergman Spaces - Hilgert, Joachim; Bertram, W. (Bull. Math. Soc. Francaise)

Poisson Lie Groups and Non-Linear Convexity Theorems - Hilgert, Joachim; Neeb, K.-H. (Math. Nachr.)

Lie Theory and its Applcations in Physics II

Positivity in Lie Theory

Wachstumsverhalten von Lösungen der $\overline{\partial}$-Gleichung auf Pseudo-Siegel-Gebieten - Hesse, Kerstin

Almost Invariant Sets in Chua's Circuit - Dellnitz, Michael; Junge, Oliver (International Journal of Bifurcation and Chaos)
Recently multilevel subdivision techniques have been introduced in the numerical investigation of complicated dynamical behavior. We illustrate the applicability and efficiency of these methods by a detailed numerical study of Chua's circuit. In particular we will show that there exist two regions in phase space which are almost invariant in the sense that typical trajectories stay inside each of these sets on average for quite a long time.

Exploring invariant sets and invariant measures - Dellnitz, Michael; Hohmann, Andreas; Junge, Oliver; Rumpf, Martin (Chaos: An Interdisciplinary Journal of Nonlinear Science)

An adaptive method for the approximation of the generalized cell mapping - Guder, Rabbijah; Dellnitz, Michael; Kreuzer, Edwin (Chaos, Solitons & Fractals)

A subdivision algorithm for the computation of unstable manifolds and global attractors - Dellnitz, Michael; Hohmann, Andreas (Numerische Mathematik)

An Uncertainty Principle for Ultraspherical Expansions - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

KANT V4 - DABERKOW, M.; FIEKER, C.; Klüners, Jürgen; POHST, M.; ROEGNER, K.; SCHÖRNIG, M.; WILDANGER, K. (Journal of Symbolic Computation)
The software packageKANT V4for computations in algebraic number fields is now available in version 4. In addition a new user interface has been released. We will outline the features of this new software package.
Keywords: Computational Mathematics; Algebra and Number Theory

On Computing Subfields - Klüners, Jürgen; Pohst, Michael (Journal of Symbolic Computation)
The purpose of this article is to determine all subfields ℚ(β) of fixed degree of a given algebraic number field ℚ(α). It is convenient to describe each subfield by a pair (h,g) of polynomials in ℚ[t] resp. Z[t] such thatgis the minimal polynomial of β = h(α). The computations are done in unramifiedp-adic extensions and use information concerning subgroups of the Galois group of the normal closure of ℚ(α) obtained from the van der Waerden criterion.
Keywords: Computational Mathematics; Algebra and Number Theory

Über die Berechnung von Automorphismen und Teilkörpern algebraischer Zahlkörper (Dissertation) - Klüners, Jürgen

Singular Unitary Highest Weight Representations via Geometric Quantization - Hilgert, Joachim (Reports on Math. Physics)

Causal Symmetric Spaces, Geometry and Harmonic Analysis